Multi-tissue single-cell analysis deconstructs the complex programs of mouse natural killer and type 1 innate lymphoid cells in tissues and circulation - McFarland, Adelle P.; Yalin, Adam; Wang, Shuang-Yin; Cortez, Victor S.; Landsberger, Tomer; Sudan, Raki; Peng, Vincent; Miller, Hannah L.; Ricci, Biancamaria; David, Eyal; Faccio, Roberta; Amit, Ido; et al. (Immunity (Cambridge, Mass.), 2021)
Natural killer (NK) cells and type 1 innate lymphoid cells (ILC1s) are heterogenous innate lymphocytes broadly defined in mice as Lin−NK1.1+NKp46+ cells that express the transcription factor T-BET and produce interferon-γ. The ILC1 definition primarily stems from studies on liver and small intestinal populations. However, NK1.1+NKp46+ cells in the salivary glands, uterus, adipose, and other tissues exhibit nonuniform programs that differ from those of liver or intestinal ILC1s or NK cells. Here, we performed single-cell RNA sequencing on murine NK1.1+NKp46+ cells from blood, spleen, various tissues, and solid tumors. We identified gene expression programs of tissue-specific ILC1s, tissue-specific NK cells, and non-tissue-specific populations in blood, spleen, and other tissues largely corresponding to circulating cells. Moreover, we found that circulating NK cell programs were reshaped in tumor-bearing mice. Core programs of circulating and tumor NK cells paralleled conserved human NK cells signatures, advancing our understanding of the human NK-ILC1 spectrum. [Display omitted] •scRNA-seq of the ILC1-NK spectrum reveals circulation- and tissue-specific programs•Unique transcriptional programs define circulating and tissue NK cells and tissue ILC1s•NK cells that are not tissue specific evince programs ranging from immature to mature•Programs of NK cells within tumors are distinct from those of other NK cells How ILC1s and NK cells differ is not clear. McFarland et al. used single-cell RNA sequencing to elucidate gene signatures of mouse ILC1-NK cells from tissues, tumors, and the circulation. Data identify unique transcription factors, phenotypic markers, and metabolic features that distinguish tissue-resident NK cells and ILC1s from circulating NK cells.